General practice careers: changing experience of men and women vocational trainees between 1974 and 1989. - Johnson, N; Hasler, J; Mant, D; Randall, T; Jones, L; Yudkin, P (1993)
The aim of this study was to consider the careers pursued by men and women general practitioner trainees following the completion of their training, and to assess changes since 1974. It was based on a postal questionnaire survey involving 995 doctors who had completed general practice vocational training in the Oxford region between 1974 and 1989. A total of 796 doctors replied to the questionnaire (498 men and 298 women, overall response rate 80%). The vast majority of ex-trainees were working in general practice at the time of the survey (men 87%, women 71%). Women were less likely to have become principals than men (75% versus 97%). Most women (71% of those completing training before 1988) reported at least one period of non-employment. While the duration of maternity leave dropped only slightly during the 15 years studied, the length of voluntary and involuntary unemployment experienced by women fell markedly. Men experienced little unemployment with no change in length of unemployment over time. Considerably fewer women than men (6% versus 13%) had become involved in teaching or training. The degree of difficulty in choosing and following a general practice career remained constant over time for women. In contrast there was a significant increase in the difficulties experienced by men. The proportion of men and women completing training in 1984-89 who found following a general practice career 'difficult or very difficult' was similar (10% of men, 13% of women). The possibility of improving these experiences, particularly by encouraging flexibility in the early years after completion of training, is discussed.